Concomitantly elevated serum matrix metalloproteinases 3 and 9 can predict survival of synchronous squamous cell carcinoma of the upper aero‐digestive tract12. Issue 6 (12th January 2012) - Wang, Wen‐Lun; Chang, Wei‐Lun; Yeh, Yi‐Chun; Lee, Ching‐Tai; Chang, Chi‐Yang; Lin, Jaw‐Town; Sheu, Bor‐Shyang
Abstract Matrix metalloproteinases (MMPs) are elevated in patients with squamous cell carcinoma (SCC) over either the head and neck (HNSCC) or the esophagus (ESCC). Synchronous SCC with both HNSCC and ESCC predispose to worse survival. This study tested if serum MMP levels correlate with clinical features and predict survival for HNSCC, ESCC, and synchronous SCC. One hundred and thirty patients with SCCs in upper aero‐digestive tract (70 ESCC, 20 HNSCC, and 40 synchronous SCC) and 74 healthy controls were assessed for serum MMP‐3, ‐7, and ‐9 titers by enzyme‐linked immunosorbent assay. The titers were validated to their correlations to clinical features and survival rates of the different SCC groups. Patients with SCCs had significantly higher serum MMP‐3, ‐7, and ‐9 titers than the controls (P < 0.001) but there was no difference among the three SCC groups. Based on the optimal MMP cut‐off values by ROC curve, elevated MMP‐3 and MMP‐9, but not MMP‐7, correlated with distant metastasis and poor survival (P < 0.05). Concomitantly elevated MMP‐3 (>14 ng/mL) and MMP‐9 (>329.3 ng/mL) independently correlated with poor two‐year survival (P = 0.002, by log rank test). Cox regression confirmed that such concomitant elevation was superior to the tumor stage of either ESCC or HNSCC in predicting survival for synchronous SCC. Serum MMPs are elevated in SCC of the upper aero‐digestive tract. Especially for synchronous SCC, concomitantly elevated MMP‐3 and MMP‐9 levels serve as better biomarkers to predict prognosis than TNM staging of ESCC or HNSCC. © 2012 Wiley Periodicals, Inc.